Freedom in the Political Ideology of Simón Rodríguez in Our-America - Pérez Jiménez, César (2026)
Freedom constitutes a central theme for examining the tensions and options linked to growing inequality and social exclusion, which once motivated the struggles for independence in the Americas. These independences materialized political and administrative aspects in a context of emancipation and armed conflicts, while the dependence of mentalities intensified, leading to the normalization of subalternities, especially at present, marked by uncertainties that undermine human freedom. The analysis focuses on the interpretation of freedom in the thought of Simón Rodríguez, based on his political, pedagogical and human vision, contributing elements to the emancipatory project in Our-America by promoting the reformulation of transformative practices in the education of people for the consolidation of the Republic. Among its objectives is the elaboration of a map on freedom as a teleological principle in Rodríguez’ pedagogical struggle, which is related to his proposal for the formation of citizens necessary to strengthen the Bolivarian republican project. Our analytical approach is of a historical-epistemological nature, focused on the contextualization of the socio-political facts intertwined with the transformations in America, and it recovers the historical challenges subscribed by Rodriguez in his liberating work.